Enhancing Intercultural Awareness through Project-Based Learning in the EFL Classroom - Sukristiningsih Sukristiningsih; Dewi V Rajagukguk (JURNAL ISLAM NUSANTARA, 2026)
This study investigates the implementation of Project-Based Learning (PBL) in a Cross-Cultural Understanding (CCU) class to enhance students’ intercultural awareness and English communication skills. The research was conducted in the English Education Department, involving undergraduate students enrolled in a CCU course. The main part of the project was an International Sharing Session, in which students spoke with speakers from different countries online to learn about their cultures, values, and daily lives. A qualitative descriptive design was used to gather data from classroom observations, students' project outputs, reflective responses, and records of learning activities. The findings indicate that PBL enhanced cultural comprehension, fostered empathy and open-mindedness, and elevated students' language and communication abilities through genuine, interactive activities. Students showed more confidence speaking English during discussions and presentations, and they also learned how to think critically and work together. Nonetheless, difficulties concerning information organization and linguistic constraints were also recognized, underscoring the necessity for instructional scaffolding and ongoing feedback. The study concludes that integrating PBL into CCU instruction effectively transforms passive learning into active inquiry, fostering the development of intercultural competence and 21st-century skills, thereby establishing it as a pertinent pedagogical approach for EFL contexts in higher education.